Eco-Friendly Transitions in Top Ten CO2 Producing Countries: A Dynamic Panel Investigation of Green Finance, Technology Transfer and Financial Development for Reducing Environmental Degradation - Shafqat, Amna; Idrees, Sadia; Zaman, Sarfraz; Ghaffar, Muniba (iRASD Journal of Economics, 2023)
This study delves into the imperative challenge of fostering eco-friendly transitions within the top 10 CO2 producing countries, employing a sophisticated dynamic panel investigation. Centered on the pivotal drivers of green finance, technology transfer, and financial development, the research seeks to comprehensively understand their synergistic role in mitigating environmental degradation. Utilizing advanced econometric techniques, notably the Nonlinear Autoregressive Distributed Lag (NARDL) model, the investigation unfolds the intricate dynamics and nonlinear relationships shaping the effectiveness of these transitions over time. The findings not only contribute empirical insights but also bear substantial policy implications. They underscore the necessity for robust regulatory frameworks and international cooperation to incentivize green investments, facilitate technology transfer, and promote financial development geared towards sustainability. In addressing the environmental challenges posed by these leading CO2 emitters, this research advocates for a holistic approach that integrates economic growth with environmental stewardship, thereby paving the way for transformative and resilient eco-friendly practices on a global scale.